Effects of prolonged NaHCO3 exposure on the serum immune function, antioxidant capacity, intestinal tight junctions, microbiota, mitochondria, and autophagy in crucian carp (Carassius auratus) - Jia Liu; Faye Zhang; Zihao Yan; Zhengyao Guo; Yuqian Lu; Baolan Yao; Yuehong Li; Wenfa Lv (Ecotoxicology and Environmental Safety)
This study investigated the effects of long-term NaHCO3 stress on serum immunity, antioxidant capacity, intestinal tight junction, intestinal microbiota, mitochondrial function and autophagy in crucian carp. A total of 240 fish (31.19 ± 1.03 g) were randomly allocated to two groups and treated with 0 mmol/L (CK) and 50 mmol/L NaHCO3 (CA) respectively, to simulate the carbonate alkaline water environment. All of the experimental fish were cultured for 8 weeks. The results showed that compared to the control group, NaHCO3 stress significantly decreased the levels of the serum immunity indices (AKP, ACP, C3, C4, IgM, LZM) and the antioxidant capacity indices (CAT, GSH-PX, SOD, T-AOC), while markedly increasing the content of MDA. Additionally, NaHCO3 influenced the mRNA expression of HSP90, Nrf2, Keap1, and HO-1. Compared to the control group, the levels of ZO-1, Claudin-2, Occludin-a, and Occludin-b mRNA significantly decreased in the NaHCO3 stress group. The levels of ATG5, ATG7, and Beclin1 mRNA and protein were significantly increased along with the levels of LC3b mRNA and the ratio of protein LC3 II /LC3 I. Compared to the control group, intestinal mitochondria in the NaHCO3 stress group were visibly swollen and largely broken, with reductions in ridges and a large proportion of the area dissolved in the matrix. The mitochondrial membrane potential and the activities of ATPase were significantly decreased, leading to mitochondria dysfunction. In addition, 3147 differentially expressed genes were identified from transcriptome sequencing, among which several genes related to mitochondria and autophagy were significantly enriched. Compared to the control group, the NaHCO3 stress decreased the ACE index and increased the abundance of Proteobacteria while decreased the abundance of Actinobacteria and Firmicutes. In conclusion, NaHCO3 induced oxidative damage, microbiota alterations, mitochondria dysfunction, and autophagy in the intestines of crucian carp. The results of this study have characterized the molecular mechanisms of intestinal injury in crucian carp caused by NaHCO3 stress, and thus provide empirical support for aquaculture in saline-alkali waters.